Risk assessment of the bedsores’ formation using available scales — a case report - Krupińska, Elżbieta (Nursing Problems / Problemy Pielęgniarstwa, 2012)
Bedsores, despite of knowledge of the factors, predisposing to their formation, methods of prevention and treatment are still a serious therapeutic and care problem. The first step in prevention is therapeutic selection of the total number of patients at risk of bedsores’ occurrence. This paper assesses the risk of decubitus for example, a branch of internal medicine, patient with five scales: Waterlow, Douglas, Norton, Braden and CBO. Interpretation of the obtained results showed that the scales, by taking into account various risk factors, gives a different classification from high risk after his absence.